2013
DOI: 10.1177/1941738113484679
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder and Athletes

Abstract: Context:Attention deficit hyperactivity disorder (ADHD) is common in the general population, and many individuals with this condition participate in sports activity at all competition levels.Evidence Acquisition:Related studies were selected through literature searches of PubMed, MEDLINE, and Cochrane databases for the years 1991 to 2011. Key search terms were ADD, ADHD, sports, athletes, athletics, guidelines, NCAA, WADA, IOC, college, concussion, diagnosis, management, treatment, evaluation, return-to-play, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 66 publications
1
57
0
Order By: Relevance
“…Goldstein et al reported mean LD group performance one standard deviation below normative group means on assessments of vocabulary (WAIS-R Vocabulary), working memory (WAIS-R Digit Span), processing speed (WAIS-R Digit Symbol), and math skills (WAIS-R Arithmetic) (Goldstein et al 2001). In athletes, specifically, LD and ADHD are associated with significantly lower scores on measures of verbal and visual memory, slower reaction time, worse impulse control, and more executive dysfunction than athletes without these diagnoses (White et al 2014; Zuckerman et al 2013). When coupled with brain trauma, athletes with LD and ADHD who perform worse on cognitive measures at baseline then tend to take longer to recover pre-injury cognitive functioning and be cleared to return to athletic participation following concussion (Waljas et al 2015).…”
Section: Neurodevelopmental Disordersmentioning
confidence: 95%
“…Goldstein et al reported mean LD group performance one standard deviation below normative group means on assessments of vocabulary (WAIS-R Vocabulary), working memory (WAIS-R Digit Span), processing speed (WAIS-R Digit Symbol), and math skills (WAIS-R Arithmetic) (Goldstein et al 2001). In athletes, specifically, LD and ADHD are associated with significantly lower scores on measures of verbal and visual memory, slower reaction time, worse impulse control, and more executive dysfunction than athletes without these diagnoses (White et al 2014; Zuckerman et al 2013). When coupled with brain trauma, athletes with LD and ADHD who perform worse on cognitive measures at baseline then tend to take longer to recover pre-injury cognitive functioning and be cleared to return to athletic participation following concussion (Waljas et al 2015).…”
Section: Neurodevelopmental Disordersmentioning
confidence: 95%
“…The neurocognitive symptoms of ADHD, including poor concentration and memory deficits, may cause academic difficulties that could threaten the academic eligibility of collegiate athletes 22. Compared with implicit (procedural) learning and implicit memory, deficits in explicit learning and explicit memory have been reported in adults with ADHD 23.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other tools that can be used to help the physician in establishing this diagnosis, such as: Connor Questionnaire, NICQH Vanderbilt Assessment Tool, DM5-criteria, SNAP IV and Pelham Scale [19].…”
Section: Diagnosismentioning
confidence: 99%